Imagery in the Journals Written by the Writing I Students Of the English Department Of Widya Mandala Catholic University Surabaya - Nonce Trisnawaty (Magister Scientiae, 2010)
Many students think that writing is a daunting task and, therefore, they cannot write a good composition and journal writing is assigned for writing improvement. One of the aspects in writing a journal is imagery. Imagery is the use of concrete words to replace the abstract ones in order to enable the readers to imagine in everything experienced by the author. This study explored the kinds of imagery which are found in the journals written by the Writing I students of Widya Mandala Catholic University Surabaya. The subjects were eleven students of Writing I. Each student submitted 4 journals. A checklist was used to organize the imagery in the journals. Not all writing journals that were analyzed exposed imagery. Visual and auditory imagery were found. There were forty seven examples of visual imagery and six examples of auditory imagery. The olfactory, gustatory and tactile imagery were not found